Creative Thinking Process Based on Wallas Model in Solving Mathematics Problem - Maharani, Hevy Risqi; Sukestiyarno, Sukestiyarno; Waluya, Budi (International Journal on Emerging Mathematics Education, 2017)
It’s difficult for junior high school’s teacher to get position and foster their students who’re still in transition in creative thinking. This study evaluated creative thinking process based on a model of Wallas (2014). Subjects were categorized into upper, middle, and low category after doing creative thinking ability test. The variable is an existence of junior high school’s students in solving a mathematics problem. Data were analyzed through classification, data representation, and conclusions. The results showed 1) 23,33% of students only reached preparation stage, called low category, 2) 60% of students reached illumination stage though students take a long time, called middle category, and 3) 16,67% of students have completed up to verification stage, called upper category. By deepening triangulation interview, right students in that category. Students in low and middle category still need assistance when experiencing obstacle in the creative thinking process, while upper category needs of enrichment materials.